mTOR Inhibition limits LPS induced acute kidney injury and ameliorates hallmarks of cellular senescence - Alessandra Stasi; Rossana Franzin; Fabio Sallustio; Alessandro Scagliotti; Paola Cappello; Elena Squiccimarro; Gianvito Caggiano; Rosa Losapio; Monica Campioni; Antonino Castellaneta; Vincenzo Cantaluppi; Claudia Curci; et al. (Scientific Reports)
Abstract Sepsis-induced acute kidney injury (AKI) can lead to chronic renal dysfunction with accelerated renal aging. Activation of the mammalian target of rapamycin (mTOR) is implicated in the initiation and progression of renal injury. This study investigates the effectiveness of the mTOR inhibitor, rapamycin, in mitigating kidney injury and explores the underlying mechanisms. AKI was induced by intraperitoneal administration of a solution containing 10 mg/kg of lipopolysaccharide (LPS) in a mouse model. Two groups of endotoxemic mice received pre- and post- treatment with rapamycin. Whole-genome DNA methylation analysis was performed on renal proximal tubular epithelial cells (RPTEC). In the LPS-induced AKI mouse model, rapamycin treatment significantly reduced creatinine levels, preserved renal parenchyma, and counteracted the endothelial-to-mesenchymal transition (EndMT) by inhibiting the ERK pathway. Whole-genome DNA methylation analysis revealed that LPS induced aberrant methylation, particularly in genes associated with premature aging, including ectonucleoside triphosphate diphosphohydrolase 1 (ENTPD1/CD39) and wolframin ER transmembrane glycoprotein (WFS1). Accordingly, endotoxemic mice exhibited decreased CD39 expression and klotho down-regulation, both of which were reversed by rapamycin, suggesting an anti-aging effect in AKI. mTOR inhibition may represent a promising strategy to prevent accelerated renal aging in LPS-induced AKI and potentially slow the progression of chronic kidney disease.